STRATEGI PUBLIC RELATIONS DALAM MEMPERTAHANKAN CITRA PERUSAHAAN MELALUI KEGIATAN CORPORATE SOCIAL RESPONSIBILITY (Studi Pada Program PT. Tiki Jalur Nugraha Ekakurir Dalam Membantu Melawan Covid-19 di Indonesia) - Fitra Darmawan (2020)
Corporate image through CSR (Corporate Social Responsibility), is not only a charitable activity but requires a company to make a real decision to estimate the impact on all stakeholders of the company, especially the environment. Therefore, a PR strategy for CSR is prepared. The purpose of this study is to find out how to process the Public Relations strategy and what programs are carried out by PT. Tiki JNE in maintaining the company's image through Corporate Social Responsibility in helping to fight the Covid-19 virus in Indonesia. This research uses descriptive qualitative research methods. This study uses a case study strategy to serve as its research strategy. Data collected in the study consisted of primary data (interviews, documentation and literature studies) and secondary (literature studies and previous research results). Researchers look for information by determining one key informant and three informants. Data analysis techniques using qualitative data analysis consisting of data collection, data reduction, data presentation and conclusions and verification. The data validity technique uses triangulation techniques. The results showed that the Public Relations strategy undertaken by PT. Tiki Path Nugraha Ekakurir is a strategy of social responsibility approach, through Corporate Social Responsibility program activities in realizing a good corporate image in the eyes of the public. In the process of Public Relations practitioners through strategic management in determining the strategy and stages of program implementation that is identifying problems, planning, implementation, evaluation. From this strategic process carried out to produce effective results to run the CSR program of PT. Tiki JNE in helping to deal with the covid-19 outbreak and creating a positive corporate image.